Experience-dependent integration of texture and motion cues to depth - Jacobs, Robert A; Fine, I (Vision research (Oxford), 1999)
Previous investigators have shown that observers’ visual cue combination strategies are remarkably flexible in the sense that these strategies adapt on the basis of the estimated reliabilities of the visual cues. However, these researchers have not addressed how observers’ acquire these estimated reliabilities. This article studies observers’ abilities to learn cue combination strategies. Subjects made depth judgments about simulated cylinders whose shapes were indicated by motion and texture cues. Because the two cues could indicate different shapes, it was possible to design tasks in which one cue provided useful information for making depth judgments, whereas the other cue was irrelevant. The results of experiment 1 suggest that observers’ cue combination strategies are adaptable as a function of training; subjects adjusted their cue combination rules to use a cue more heavily when the cue was informative on a task versus when the cue was irrelevant. Experiment 2 demonstrated that experience-dependent adaptation of cue combination rules is context-sensitive. On trials with presentations of short cylinders, one cue was informative, whereas on trials with presentations of tall cylinders, the other cue was informative. The results suggest that observers can learn multiple cue combination rules, and can learn to apply each rule in the appropriate context. Experiment 3 demonstrated a possible limitation on the context-sensitivity of adaptation of cue combination rules. One cue was informative on trials with presentations of cylinders at a left oblique orientation, whereas the other cue was informative on trials with presentations of cylinders at a right oblique orientation. The results indicate that observers did not learn to use different cue combination rules in different contexts under these circumstances. These results are consistent with the hypothesis that observers' visual systems are biased to learn to perceive in the same way views of bilaterally symmetric objects that differ solely by a symmetry transformation. Taken in conjunction with the results of Experiment 2, this means that the visual learning mechanism underlying cue combination adaptation is biased such that some sets of statistics are more easily learned than others.